PENGEMBANGAN KEMAMPUAN BAHASA ARAB MELALUI METODE QIROAH - Lulu Al Mukarromah; Acep Mulyadi; Aulia Ayu Rohayah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
Community service is a form of education by providing learning experiences with the community, identifying potential and dealing with problems, so that it is expected to be able to develop community potential and concoct solutions from the community. This community service was carried out in Karangharja Village, Pebayuran District, Bekasi Regency. This activity implements a community service programme, namely Arabic language learning using the reading and listening method to develop Arabic. Arabic is an important need, because it has become the language of religion, the language of official communication between nations, the language of the Islamic world, the language of culture, the language of science and technology, and so on. The method of implementing the service applies the method of socialisation and practical training in the pronunciation of Arabic vocabulary. It can be concluded that during the training, the community was able to recognise Arabic properly and correctly.